1997
DOI: 10.1002/(sici)1096-8628(19970211)68:4<391::aid-ajmg3>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Tricho-hepato-enteric syndrome: Further delineation of a distinct syndrome with neonatal hemochromatosis phenotype, intractable diarrhea, and hair anomalies

Abstract: We report on two sibs with syndromal congenital iron storage disease. Prenatal symptoms were IUGR, hydramnios, and placental hyperplasia. Clinical anomalies included hypertelorism and sparse, thin, curly hair (trichomalacia). Clinical course was marked by intractable diarrhoea, with normal histological and enzymological studies, cholestatic jaundice, hepatomegaly appearing after 30 days, and progressive liver failure, leading to death after a few months. The only metabolic anomaly was progressive hypermethioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 17 publications
(17 reference statements)
5
38
0
2
Order By: Relevance
“…Occasionally, the NH phenotype can arise from non-GALD diseases including perinatal infection, 3,24,25 trisomy 21, 14,26À28 mitochondrial DNA depletion due to deoxyguanosine kinase deficiency (DGUOK gene mutations), [29][30][31] bile acid synthetic defect delta 4-3-oxosteroid 5 beta-reductase deficiency (SRD5B1 mutations), [32][33][34] GRACILE syndrome (BCS1L mutation), 35,36 myofibromatosis, 14 tricho-hepato-enteric syndrome 37,38 and Martinez-Frias syndrome. 39 In cases of trisomy 21, transient megakaryocytic leukemia may explain the NH phenotype.…”
Section: Causes Of Neonatal Hemochromatosis Phenotype Other Than Gestmentioning
confidence: 99%
“…Occasionally, the NH phenotype can arise from non-GALD diseases including perinatal infection, 3,24,25 trisomy 21, 14,26À28 mitochondrial DNA depletion due to deoxyguanosine kinase deficiency (DGUOK gene mutations), [29][30][31] bile acid synthetic defect delta 4-3-oxosteroid 5 beta-reductase deficiency (SRD5B1 mutations), [32][33][34] GRACILE syndrome (BCS1L mutation), 35,36 myofibromatosis, 14 tricho-hepato-enteric syndrome 37,38 and Martinez-Frias syndrome. 39 In cases of trisomy 21, transient megakaryocytic leukemia may explain the NH phenotype.…”
Section: Causes Of Neonatal Hemochromatosis Phenotype Other Than Gestmentioning
confidence: 99%
“…1 44 cases have been published between 1982 and 2012. Literature reviewed showed that 9 clinical signs are associated with THE-S. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Three are constant: intractable diarrhea, facial dysmorphism and hair abnormality. Two are very frequent (more than 90%): IUGR and immunodeficiency; 2 are frequent: skin abnormalities and liver disease and 2 are rare: congenital cardiac defects and platelet anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Two are very frequent (more than 90%): IUGR and immunodeficiency; 2 are frequent: skin abnormalities and liver disease and 2 are rare: congenital cardiac defects and platelet anomaly. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The phenotypic presentation of THE-S is heterogeneous, and ranges from mild to severe form, which is characterized with long-term parenteral nutrition, and in some patients, typically it lasts for months to years, to achieve adequate nutrition and growth. 12 However, longterm parenteral nutrition should not be started in patients with concomitant liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Verloes y sus colegas describieron la diarrea fenotípica de la infancia o síndrome tricohepatoentérico como diarrea intratable con fenotipo de hemocromatosis neonatal y anormalidades en el pelo. 3 Se han agrupado en un solo síndrome porque las características clínicas principales son idénticas. Varios autores han identificado mutaciones en el gen TTC37 en 21 individuos con el análisis de mapeo homocigoto después de realizar arreglo de polimorfismo de nucleó-tido único (SNP por sus siglas en inglés); dicho gen fue identificado en el locus 5q14.3-5q21.2 y codifica una proteína repetida, tetratricopeptí-dica no caracterizada llamada thespin (proteína del síndrome tricohepatoentérico por sus siglas en inglés).…”
Section: Discussionunclassified